#### Answer

26

#### Work Step by Step

Because this is a kite:
RS = RV
ST = TV
Therefore:
RS = y
RS = 2x - 4
ST = y - 3
ST = x - 1
Since RS equals both 2x - 4 and y, 2x - 4 and y equal each other. The same goes for ST:
2x - 4 = y
x - 1 = y - 3
x - 1 is equal to y - 3, so if 2x - 4 = y, 2x - 4 - 3 = x - 1:
2x - 4 - 3 = x - 1
Simplify:
2x - 7 = x - 1
Add 7 to both sides:
2x = x + 6
If 2x = x + 6, 2x $\div$ 2 = 6. So 2x = 12 and:
x = 6
Now we substitute 6 for x when adding together each side:
2(6) - 4 + 2(6) - 4 + 6 - 1 + 6 - 1
Simplify
8 + 8 + 5 + 5 = 26